IL‐1β induces thymic stromal lymphopoietin and an atopic dermatitis‐like phenotype in reconstructed healthy human epidermis. Issue 2 (6th April 2017) - Bernard, Marine; Carrasco, Cédric; Laoubi, Léo; Guiraud, Béatrice; Rozières, Aurore; Goujon, Catherine; Duplan, Hélène; Bessou‐Touya, Sandrine; Nicolas, Jean‐François; Vocanson, Marc; Galliano, Marie‐Florence
Abstract: Atopic dermatitis (AD) is a common skin inflammatory disease characterized by the production of thymic stromal lymphopoietin (TSLP) and marked TH 2 polarization. Recent studies suggest that IL‐1β contributes to the development of AD skin inflammation. Here, we have investigated the impact of IL‐1β signalling on the epidermal homeostasis of both healthy subjects and AD patients [with functional filaggrin ( FLG ) alleles], with particular attention to TSLP production and keratinocyte differentiation. In healthy reconstructed human epidermis (RHE), IL‐1β promoted (i) robust secretion of TSLP in an NF‐κB‐dependent manner and (ii) a significant decrease in the expression of filaggrin and other proteins of the epidermal differentiation complex. These effects were prevented by treatment of RHE with the anti‐IL‐1β mAb canakinumab and by the IL‐1 receptor antagonist anakinra. Interestingly, RHE generated from AD donors behaved like that of healthy individuals and showed comparable responses to IL‐1β signals. Collectively, our results suggest that IL‐1β may be an early key mediator for the acquisition of an AD phenotype through induction of TSLP and alteration of the epidermal homeostasis. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.